Case report: pregnancy outcome following unilateral uterine artery embolisation for uterine arterio-venous malformation. (16th November 2010) - Khoo, CL; Stephen, GL; Davies, JA; Bellis, AJ
Abstract : Uterine arterio-venous malformation (UAVM) is an extremely rare but serious cause of genital tract bleeding and experience in its management is limited. Uterine artery embolisation (UAE) has been reported to be a successful treatment in women seeking to retain their fertility potential. However, data on pregnancy outcomes following UAE for UAVM are scarce with less than 30 such cases reported. The authors report the pregnancy outcome of a 29-year-old gravid six para three who conceived within 3 months of treatment with unilateral UAE for profuse vaginal bleeding due to UAVM. She had three previous normal vaginal deliveries, with all of her babies being at least 3.23 kg at birth. Apart from being on enoxaparin, due to a history of bilateral deep vein thrombosis, and methadone, this pregnancy was otherwise uneventful. She presented in spontaneous labour at 40-weeks-gestation and delivered a live healthy male infant weighing only 2.25 kg. Blood loss at delivery was only 150 ml. Although successful outcomes have been reported, it is essential that clinicians counsel patients that a pregnancy following UAE is still at risk of poor outcomes such as increased spontaneous abortion and stillbirth risk, as well as intrauterine growth retardation. Appropriate monitoring should be performed taking these into consideration.